AWARENESS ON HYPERTHYROIDISM AMONG DENTAL STUDENTS - Hafiz, Nauma; Ganapathy, Dhanraj; Rohinikumar, Subhashree (International Journal of Psychosocial Rehabilitation, 2020)
Thyroid disease is a global health issue and are amongst the most common endocrine disorders prevalent worldwide. The prevalence rate of thyroid diseases depends on the geographical location, age group, ethnicity, and most importantly the iodine intake of the population Dentists should be aware of its oral manifestations prior to starting treatment. Hence there is a need to understand and bring about awareness regarding hyperthyroidism. To assess awareness on hyperthyroidism among dental students. An online survey with pretested and validated questionnaire consisting of 10 questions testing awareness of hyperthyroidism were circulated among 100 undergraduate dental students. The Questions regarding adverse effects and clinical tests and symptoms of hyperthyroidism and its awareness were included in the survey. Data was collected, analyzed and tabulated. 83% consider TSH, T3 and T4 to be important in the diagnosis of hyperthyroidism. 33% of the volunteers were aware of TSH levels in hyperthyroidism. 50% felt hypothyroidism is evenly distributed between both genders. 17% consider osteoporosis of the jaws to be the major oral manifestation. It is found from this study that there is acceptable knowledge on hyperthyroidism amongst dental students however there is need to increase the recognition and management of the condition. Dental treatment modifications may become necessary for patients who are under medical management for thyroid disorder and follow-up for a thyroid condition even though there are no direct life-threatening condition.